Laboratory experiments on counter-propagating collisions of solitary waves. Part 2. Flow field. (19th August 2014) - Chen, Yongshuai; Zhang, Eugene; Yeh, Harry
Abstract: In the companion paper (Chen & Yeh, J. Fluid Mech., vol. 749, 2014, pp. 577–596), collisions of counter-propagating solitary waves were studied experimentally by analysing the measured water-surface variations. Here we study the flow fields associated with the collisions. With the resolved velocity data obtained in the laboratory, the flow fields are analysed in terms of acceleration, vorticity, and velocity-gradient tensors in addition to the velocity field. The data show that flow acceleration becomes maximum slightly before and after the collision peak, not in accord with the linear theory which predicts the maximum acceleration at the collision peak. Visualized velocity-gradient-tensor fields show that fluid parcels are stretched vertically prior to reaching the state of maximum wave amplitude. After the collision peak, fluid parcels are stretched in the horizontal direction. The boundary-layer evolution based on the vorticity generation and diffusion processes are discussed. It is shown that flow separation occurs at the bed during the collision. The collision creates small dispersive trailing waves. The formation of the trailing waves is captured by observing the transition behaviour of the velocity-gradient-tensor field: the direction of stretching of fluid parcels alternates during the generation of the trailing waves.